The possibility of achieving sustainable agricultural development in Iraq - مجيد عمر حميد (Journal of Economics and Administrative Sciences, 2020)
Purpose – The research aims to introduce sustainable agricultural development and the possibility of its application in the Iraqi agricultural sector by setting a proposed plan by which to overcome obstacles and then advance the reality of the agricultural sector in Iraq and the fact that the process of achieving agricultural development in the Iraqi agricultural sector today has become more sophisticated and more distant than before. The study adopted the descriptive analytical approach based on the principles of economic theory to clarify the shortcomings in the process of harmony between the three main elements of sustainable agricultural development, which are natural, social, and manufactured. Findings – The most important obstacles facing the agricultural sector in Iraq were identified, a plan was also developed to overcome these obstacles and achieve sustainable agricultural development in Iraq, and that is by applying modern agricultural technology. Practical implications – Review the reality of the agricultural sector, supported by official data on the volume of production and productivity and other important indicators, as well as a practical plan based on the introduction of advanced technology in agriculture. Originality/value – The study is unique in offering sustainable agricultural development by linking its three main components, which are the natural, social and manufactured environment, explaining the process of interdependence and overlap between these elements and its positive impact on the reality of the agricultural sector in particular and the national economy in general.